TOLERANSI BEBERAPA GENOTIPE Vigna umbellata (THUMB.) TERHADAP SUHU TINGGI PADA BERBAGAI TAHAP PERTUMBUHAN - Yuyu Suryasari Poerba; Fauzia Syarif (BERITA BIOLOGI, 1999)
Degree of electrolyte leakage (EL) from leaf tissue after exposure to high temperature has been used as an indicator of heat tolerance. Inthe present study, EL was measured in an attempt to estimate heat tolerance of Viana umbellata (Thumb.) genotypes at three different growth phases. The degree of heat injury is significantly different among the three growth phases and among the genotypes as well as their interaction. However, the degree of heat injury tends to increase over the plant growth. The 18 genotypes of V. umbellata shows moderate genetic variability as shown by its value of genetic variance (46,25 Â±16,35), phenotypic variance (85,37 Â±27,60), and coefficient of genetic variation (26,36%).